Implementation of Hand Tractor Control Device Remotely Using Flysky Fs-I6 Remote Control - Wahyudi, Riyan; Ariandi, Muhamad (PROtek : Jurnal Ilmiah Teknik Elektro, 2024)
The use of hand tractors for agricultural land processing still causes several problems such as work fatigue and ergonomic problems for the operator. From these problems the author has the idea to build a tool that can be attached to a hand tractor so that the hand tractor can be controlled using a remote control. The purpose of this final project is to make a remote hand tractor controller, find out the performance of the tool, and find out how the tool works. The method used consists of system design, tool making, and testing. In the hardware part, the main control uses an ATmega328 microcontroller on an Arduino nano board, flysky fs-i6 remote control as a remote command sender input, servo motor as the output of the gas mechanical drive on the tractor disel, motor driver as an output amplifier to drive the DC power window motor that pulls the tractor clutch, solar panel for battery charging, pzem sensor to measure the power coming out of the solar panel. To design the software schematic used is fritzing software, and for program creation using Arduino IDE software. Based on the test results of the tool installed on the hand tractor, it shows that this tool has been successful and the tractor can be controlled remotely. The remote tractor controller works with a power supply voltage in the range of 12 volts DC. The receiver on the tool works with a voltage of 5.0 volts DC with a transmission range that can cover a distance of up to 1000 m. The servo motor works at a voltage of 5.0 volts DC. The mechanical clutch is capable of being pulled by a DC power window motor that works with a voltage of 12 volts DC.